THE EFFECT OF HIGH-INTENSITY FOCUSED ELECTROMAGNETIC (HIFEM) THERAPY ON PATIENTS WITH URGE URINARY INCONTINENCE - Daryanto, Besut; Nur Budaya, Taufiq; Satria, Hikmat (Indonesian Journal of Urology, 2026)
Objective: This study aims to determine the effect of HIFEM on OABSS and pad usage through the Voiding Diary. Material & Methods: An experimental study with pre and post-test. Patients will be given a questionnaire before and after undergoing HIFEM therapy for six sessions, and be followed for one month. Data analysis was carried out using SPSS software. Paired T-test was used for data with normal distribution, while the Wilcoxon Non-parametric test was used for data which is not normally distributed. Data are considered statistically significant if the p-value <0.05. Results: Twenty-eight patients completed the study. After six HIFEM sessions, the mean OABSS significantly decreased from 12.89 ± 1.03 to 11.61 ± 1.59 (p < 0.001), and pad usage reduced from 8.39 ± 1.20 to 2.82 ± 1.56 (p < 0.001). Conclusion: Six sessions of HIFEM therapy were associated with a decrease in OABSS and pad use in patients with urinary incontinence. But OABSS did not significantly reduce in patient with DM and HT. Keywords: HIFEM, urinary incontinence, OABSS.